The Underground Publication Perspektyvos (1978–1981): The Beginning of Intellectual Samizdat in Lithuania - Klumbys, Valdemaras (Genocidas ir rezistencija, 2002)
When samizdat appeared (in 1972 Lietuvos Katalikų Bažnyčios Kronika came out for the first time), resistance to soviet occupation reached higher level, became more organised, in Lithuania. However, samizdat of national and catholic character did not satisfy some of dissidents, especially those who sympathized ideas of democracy and human rights suggested by the Russian samizdat, due to its occasional intolerance and narrowness. This reason was the main for appearance of a new underground publication the Perspektyvos in 1978. The publisher of this publication was a docent of Vilnius University Vytautas Skuodis helped by Albertas Zvicevičius, Stasys Stungurys, Albertas Žilinskas, Ramutis Bonifacas Mikšys and Povilas Pečeliūnas. This publication was the only monthly in Lithuania. Many translations from the Russian samizdat (translations comprised one third of the publication, mostly written by Andrei Sakharov), articles from Lithuanian samizdat, press of emigrants, excerpts from foreign radio stations’ broadcasts and also articles and documents by Lithuanian dissidents were published in the Perspektyvos. Publishers declared legality of their activities and their goal to change the system in the process of democratization, i.e. they as if repeated principles of the Russian liberal samizdat. However, undeclared goal of the publishers was the independence of Lithuania. They published unchanged material of various deviations and various opinions they could get and this way they broke a certain censorship which had been characteristic to the Lithuanian samizdat before.